Ethnography Of Communication Of Marcus Flavious Aquila, The Major Character In The Eagle Movie (2011) - Indriani, Eri, Prof. Dr. Endang Fauziati, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This research aims for revealing and clarifying ethnography of communication of Marqus Flavious Aquilla, the major character in The Eagle movie (2011) by Kevin Macdonals using SPEAKING grid.The type of research conducted by the researcher is descriptive qualitative method. The reason of writer conducts this research is to identify the ethnography of communication found in the Marqus utterances. The object of the research is ethnography of communication of Marqus Flavious Aquilla as major character in The Eagle Movie (2011). The data of this research are utterances or dialogues which exist of settings, participants, ends, acts, keys, instruments, and genres by Marqus Flavious Aquilla in The Eagle Movie. The data source is taken from The Eagle movie by Kevin Macdonald. The method of collecting data employed by writer is analyzing document and conducting observation toward the movie. The method of data collection employed by writer is analysing document and conducting observation toward the movie. The writer does the following steps; watching the movie repeatedly, for understanding the movie deeply, collect the data of Marqus dialogues, noting the data on notebook, classifying the data based on the criteria. In analyzing the data, the writer uses Dell Hymes speaking theory for analyzing the ethnographic of communication of Marqus Flavious Aquilla. It means that the writer analyzes them as referred to the sociolinguistic context as follows: collecting the data from the Eagle movie, determining the Marqus dialogue based on the Dell Hymes theory, analyzing the ethnographic of communication of Marqus dialogues, drawing conclusion and proposing suggestion toward the data. The writer conducts research Ethnography of Communication of Marqus Flavious Aquilla, The Major Character in The Eagle movie (2011) which uses SPEAKING grid by Hymes for analyzing. SPEAKING grid of ethnography of communication is Settings or Scene, Participants, Ends, Keys, Instruments, Genre. The writer doesn‟t involve the term "norm‟ because particular reason which is discussed in previous chapter. The clear description of Ethnography of communication by Marqus is as follows, 1. This research findings ethnography of communication of Marqus is as follows: Setting of ethnography of communication by Marqus dialogues is at garrison, at uncle‟s home, at jungle, at government office. The scene of particular settings is firstly at garrison the scene of Marqus is surprised, secondly the scene is emotional toward the uncle‟s home setting. Thirdly x the scene at the jungle is a firm. The last is at government office, the scene is happy. 2. Participant of Marqus communication is the sender and receiver. The sender is as commander, as ex society member, as employer, and as friend while the receiver is as ex-commander, as employer, and as patient. 3. End of communication by Marqus is to command, to get honor, to get information, and to believe. 4. Act sequences of Marqus communication is commanding, getting the honor, getting information, believing. 5. Keys of Marqus communication consists of two aspect, those are tone and manner. The tone of Marqus utterances is flat, tense, worried, and intimidate, while manner of Marqus utterances is low intonation and high intonation. 6. Instruments of Marqus communication involves two aspect, those are verbal communication and non-verbal communication. The verbal communication consists of formal style and informal style, while the nonverbal communication is by lifting the thumb. 7. Genre of Marqus communication is command, and prayer. According to the research findings in chapter four, so the writer concludes briefly of the research. Marqus communication has been influenced by the society which is gaining the rumor, many more contribution of Roman society in growing Marqus intellectuality. The intellectuality relate to cognitive process who can affects somebody in delivering speech. Rome is civilized people who like to establish, expand land territory for colonialism. The people like to employ the savage, so it affects the paradigm of Marqus toward the tribe people outside of Rome. Marqus is tension and high intonation when he delivers speech. Temperamental and emotional person when talk to other is his character. Being commander who ambitiousness to find the honor back to his family with struggle not to let dishonor himselves in leading. The social class of Rome culture toward the savage also makes him elevates the prestige. Especially the great cause of family about the honor, they are government military legion from the grandfather so it flows military blood to Marqus which has higher position than generally society member. He sees that the common people must follow what he decides to. Hymes delivers SPEAKING (settings, participants, ends, act, keys, instruments, norms, and genre) aspect in analyzing communicative events. The writer eliminates an aspect from SPEAKING in analyzing the data. The writer removes "norms". The reason is norms can‟t be analyzed from movie data. It needs in real society data communication in particular time, more than just a section time.